Enhanced antibacterial effect of antibiotics by the essential oil of Aloysia gratissima (Gillies & Hook.) Tronc. and its major constituent beta-caryophyllene - Eduardo L. Santos; Priscilla R. Freitas; Ana Carolina J. Araújo; Ray S. Almeida; Saulo R. Tintino; Cicera Laura R. Paulo; Ana Cristina A. Silva; Luiz E. Silva; Wanderlei do Amaral; Cícero Deschamps; José Pinto Siqueira Junior; José Maria Barbosa Filho; et al. (Elsevier, 2021)
Background: Aloysia gratissima (Verbenaceae), popularly known as bee-brush or whitebrush, has been widely used in Brazilian folk medicine as analgesic, expectorant and antimicrobial. Phytochemical studies have identified β-caryophyllene as one of the major components of the essential oil of this plant. This bioactive sesquiterpene has been shown to have anti-inflammatory and antibacterial activities. Purpose: The present study aimed to characterize the chemical profile and evaluate the antibacterial and antibiotic-enhancing activities of the essential oil obtained from Aloysia gratíssima (EOAG) and β-caryophyllene. Methods: The phytochemical analysis was performed by gas chromatography coupled to mass spectrometry (GC-MS). The antibacterial activity against Pseudomonas aeruginosa 24, Staphylococcus aureus 10, and Escherichia coli 06 was assessed by determining the minimum inhibitory concentration (MIC) using the broth microdilution method. The potentiation of the antibiotic activity by the EOAG and the β-caryophyllene was performed using the MIC evaluation of the antibiotic alone or in association with the essential oil and its main compound. To evaluate the minimum reduction of the drug concentration necessary, the Dose Reduction Index (DRI) was calculated. Results: A reduction in the MIC of the antibiotics against strains treated simultaneously with the essential oil or β-caryophyllene was observed. The GC-MS analysis of the EOAG identified 30 compounds, including β-caryophyllene as the major component. Both OEAG and β-caryophyllene presented antibacterial activity against S. aureus, in addition to potentiating the action of norfloxacin against S. aureus, P. aeruginosa, and E. coli. Conclusions: These substances also reversed the antibiotic resistance to gentamicin and erythromycin against of S. aureus and P. aeruginosa, respectively.